PEMODELAN DAN SIMULASI DISTRIBUSI MUATAN PEMBAWA IONIK PADA ZAT PADAT ANISOTROPIK FIBER DUA DIMENSI - Rahardi, Susanto (Balai Besar Bahan dan Barang Teknik, 2089)
Â One of important aspects in material engineering is the effect of morphology on the properties of material. In lithium-ion batteries technology, morphology of active material at electrode influences the propagation of ionic charge carrier inside the batteries.Â In this paper, we studied the properties of a solid state material consisting of an anisotropic fiber granules where ions propagate. The propagation mechanism is difusion process and affected by an external electric field on the material. Mathematical modelling and simulation was made to describe the influence of the randomness of anisotropic fiber granules on the charge distribution. The result of simulation indicates that the turtuosity decreases ionic migration. Â